Требования к контактным материалам коммутационных устройств - Волкова, Ольга Григорьевна (НТУ "ХПИ", 2015)
Предложено перейти от использования в конструкциях сильноточных электрических аппаратов медных сплавов в качестве электроконтактных материалов на порошковые материалы. Представлен анализ состава порошкового материала и даны рекомендации по количественному составу легирующих компонентов в структуре медной матрицы. Отмечено, что сложное легирование медной порошковой матрицы проявляется эффектом синергетики, обусловленной каркасной структурой из легирующих компонентов, что придает образованным твердым растворам при достаточной пластичности более высокую прочность.

It is proposed to move from use in the construction of high-current electrical apparatus of copper alloys as electrical contact materials to powder materials. An analysis of the composition of the powder material is presented, recommendations on the quantitative composition of the alloying components in the structure of the copper matrix are given. It is noted that complex alloying copper powder matrix is manifested by synergetic effect due to the carcass structure of the alloying components, which gives higher strength of formed solid solutions with sufficient plasticity.
Requirements for contact materials of switching devices
Keywords: электрические контакты; порошковый материал; легирующий компонент; твердая смазка; электропроводность; теплопроводность; electrical contacts; powder material; alloying component; solid lubricant; electrical conductivity; thermal conductivity